Effects of interferential current transcutaneous electrical sensory stimulation in patients with severe dementia and dysphagia in long-term care facilities - Yoshiko Hara; Ayako Nakane; Yu Yoshizumi; Kazuharu Nakagawa; Kohei Yamaguchi; Kanako Yoshimi; Haruka Tohara (BMC Geriatrics)
Abstract Background The aim of the study was to ascertain the efficacy of interferential current-transcutaneous electrical sensory stimulation (IFC-TESS) in treating patients with severe dementia accompanied by dysphagia who reside in long-term care facilities. Methods We conducted a comparative intervention study. Forty-four patients with severe dementia and dysphagia in a long-term care facility were administered IFC-TESS for 15 min twice daily, 5 days a week. The clinical findings before and after 3 weeks of intervention were compared. Results The study participants showed significant improvement in oral calorie intake after the intervention (p<0.05). The oral calorie intake indicated an improved nutritional state. Conclusions IFC-TESS may be effective in improving oral intake by patients with dementia. Trial registration The trial was registered at UMIN-CTR under the identifier UMIN000032262 (Registration date: 16/04/2018).